Comparison of Three Different Slip Meters under Various Contaminated Conditions - Jungsoo Kim (Elsevier, 2012)
Objectives: To challenge the problem of slipperiness, various slipmeters have been developed to assess slip hazard. The performance of in-situ slipmeter is, however, still unclear under the various floor conditions. The main objectives of this study were to evaluate the performance of three kinds of slipmeters under real conditions, and to find their dynamic and kinematic characteristics, which were compared with gait test results. Methods: Four common restaurant floor materials were tested under five contaminants. Slipmeters and human gaits were measured by high speed camera and force plate to find and compare their dynamic and kinematic characteristics. Results: The contact pressures and built-up ratio were below those of subjects. The sliding velocity of British Pendulum Tester was above those of subjects, while those of BOT-3000 and English XL were below those of subjects. From the three meters, the English XL showed the highest overall correlation coefficient (r = 0.964) between slip index and Ra, while the rest did not show statistical significance with surface roughness parameters (Ra, Rz). The English XL only showed statistical significance (p < 0.01) between slip index and contaminants. The static coefficient of friction obtained with the BOT-3000 showed good consistency and repeatability (CV < 0.1) as compared to the results for the BPT (CV > 0.2) and English XL (CV < 0.2). Conclusion: It is unclear whether surface roughness can be a reliable and objective indicator of the friction coefficient under real floor conditions, and the viscosity of contaminants can affect the friction coefficient of the same floors. Therefore, to evaluate slipperiness, the performance of the slipmeters needed to improve.